Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1189/jlb.0702371
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid activates phospholipase D in human neutrophils; essential role of endogenous leukotriene B4 and inhibition by adenosine A2A receptor engagement

Abstract: We report in human neutrophils (PMN) that phospholipase D (PLD) was stimulated by micromolar concentrations of arachidonic acid (AA) and nanomolar concentrations of leukotriene B(4) (LTB(4)), and eicosapentaenoic acid was inactive. The stimulatory effect of AA occurred only when adenosine was eliminated from PMN suspensions or when PMN were incubated with adenosine A(2A) receptor antagonists. The mechanism of AA-induced PLD activation was investigated. The results show that AA- and LTB(4)-induced PLD activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…PLD activity was not inhibited by pyrrophenone in fMLP-activated PMN. In contrast, the data presented herein showed that pyrrophenone inhibited PLD activity in thapsigargin-activated PMN, an effect that could be attributed to inhibition of cPLA 2 a and biosynthesis of LTB 4 , which acts as the direct activator of PLD in these experimental conditions (Grenier et al, 2003). These results demonstrate that pyrrophenone has no direct inhibitory effect on PLD.…”
Section: Discussioncontrasting
confidence: 90%
“…PLD activity was not inhibited by pyrrophenone in fMLP-activated PMN. In contrast, the data presented herein showed that pyrrophenone inhibited PLD activity in thapsigargin-activated PMN, an effect that could be attributed to inhibition of cPLA 2 a and biosynthesis of LTB 4 , which acts as the direct activator of PLD in these experimental conditions (Grenier et al, 2003). These results demonstrate that pyrrophenone has no direct inhibitory effect on PLD.…”
Section: Discussioncontrasting
confidence: 90%
“…These results are in good agreement with those of our previous study showing that 22:6n-3, but not 20:5n-3, stimulated the PLD activity of human mononuclear cells [7]. 20:5n-3 was also found inactive toward the PLD activity of human neutrophils, whereas arachidonate induced a 2-fold increase at micromolar concentrations [10].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we have previously shown that docosahexaenoic acid (22:6n-3) [7,8] or the monohydroxylated derivative of arachidonic acid (20:4n -6), 12-hydroxy eicosatetraenoic acid (12-HETE) [9] stimulated the PLD activity of ConA-stimulated human lymphocytes. Several other groups have reported PLDdependent FA effects in neutrophils [10], smooth muscle cells [11] or macrophages [12]. The functional consequences of PLD activation on mitogenic signaling clearly depends on the cell type considered.…”
Section: Introductionmentioning
confidence: 97%
“…Different studies reported an enhancing effect of docosahexaenoic acid (DHA) (Bechoua et al, 1998;Diaz et al, 2002) and the monohydroxylated derivate of arachidonate, hydroxyeicosatetraenoic acid (Meskini et al, 1995) on Con A-stimulated PLD activity in human lymphocytes. Other studies described PLD-dependent effects of fatty acids in neutrophils (Grenier et al, 2003), smooth muscle cells (Askari et al, 2002) or macrophages (Wang and Oram, 2005). Examination of PLD activity in intestinal cells showed that the enzyme activity was stimulated by linolenate (LA) and g-linolenate, with LA being more effective (Awad et al, 1994).…”
mentioning
confidence: 99%